Information Systems and Technologies for Quality Management of Educational Projects - Chernenko Oleksandr (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
The article is dedicated to studying the role of information systems and technologies in managing the quality of educational projects in higher education institutions of Ukraine. The aim of the article is to characterize the main modern information systems and technologies that can be applied in quality management of educational projects. The research was conducted using the following scientific methods: analysis and synthesis, induction and deduction, comparison, analogy, classification, and generalization. Current trends in the implementation of digital technologies in the educational process are analyzed, including learning management systems, data analytics, adaptive learning, and immersive technologies. The potential of information technologies for improving the efficiency of educational projects, personalizing learning, and optimizing administrative processes is examined in the context of global challenges and specific conditions of the Ukrainian education system. Based on the analysis of scientific literature and practical experience, a classification of information systems and technologies for quality management of educational projects is proposed, and methodological recommendations for their effective application in higher education are developed. The implementation of modern technological solutions (LMS, SIS, ERP and MRP, LAS, ISO 9001, TQM, cloud technologies, databases, mobile applications, artificial intelligence, and machine learning) facilitates the optimization of management processes in creating a digital educational environment, ensuring improved communication between participants in the educational process, and promoting group research work. The introduction of information systems and technologies in higher education contributes to ensuring proper quality of education according to the standards of the Ministry of Education and Science of Ukraine, thanks to better personalized learning, feedback, optimization of administrative processes to focus on strategic issues, expanding access to education through online and blended learning, widespread use of interactive teaching methods, flexible organization of group research work of students, as well as improving management decision-making based on processed data, which contributes to more effective management of educational projects in higher education institutions. The research results can be used to improve education quality management processes and enhance the competitiveness of Ukrainian higher education institutions in the context of digital transformation of the educational environment.